Respon Profesi Akuntan Manajemen Indonesia Terhadap Pergeseran Peran Profesi Tersebut Dalam Era Teknologi Informasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The shifting role of management accounting profession has demanded a radical change on the core competence of the profession. The Management Accountant Compartment of Indonesian Institute of Accountants has responded strategically to the change, in order for the profession to adapt to the new environment. It published a very fundamental statement on management accounting, concerning the framework for formulating the competencies of management accounting profession. Using the framework, then, it formulated the new roles and the core competencies of management accounting profession needed to fulfill the roles. This article describes the strategic steps taken by the Indonesian management accounting professional organization in responding to the radical change in its environment